The Effect of Work Motivation and Quality of Work Life on Organizational Commitment and Performance of Employees at the Department of Industry and Trade in Bali Province - Kadek Yustisi Ari Anggitaning; I Ketut Setia Sapta; Nengah Sudja (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
This study aims to determine the effect of Work Motivation and Quality Of Work Life (QWL) on Organizational Commitment and Employee Performance at the Bali Province Industry and Trade Office. This research was conducted at the Department of Industry and Trade of the Province of Bali with the number of samples used as many as 80 people using the saturated sampling method or total sampling. Collecting data using a questionnaire. All data obtained from the distribution of questionnaires are suitable for use, then analyzed using Structural Equation Modeling (SEM) based on variants known as Partial Least Square (PLS) analysis. The results show that (1) Work Motivation has a significant and positive effect on Employee Performance, (2) Quality of Work Life (QWL) has a positive and significant effect on Employee Performance, (3) Work Motivation has a positive and significant effect on Organizational Commitment, (4) Quality of Work Life (QWL) has a positive and significant effect on Organizational Commitment, (5) Organizational Commitment has a positive and significant effect on Employee Performance.